Bevacizumab as a surgery-sparing agent for spinal ependymoma in patients with neurofibromatosis type II: Systematic review and case. (April 2021) - Snyder, M. Harrison; Ampie, Leonel; DiDomenico, Joseph D.; Asthagiri, Ashok R.
Highlights: NF2 patients suffer from cumulative morbidity; non-operative management should be prioritized. Bevacizumab has been successfully used to manage ependymomas in the NF2 population. This agent can help defer surgery for patients at risk of cumulative surgical morbidity. Abstract: Neurofibromatosis type 2 (NF2) is a rare, hereditary tumor syndrome, often requiring repeated surgeries for multiple lesions with significant cumulative morbidity. As such, non-operative management should be considered when possible for this patient population. The aim of this study is to provide a systematic review of the literature regarding this treatment strategy. A descriptive case of a patient in whom bevacizumab treatments enabled over 15 years of surgical postponement for a symptomatic spinal cord ependymoma is also provided. Evidence suggests that bevacizumab is a reasonable surgery-deferring option for cystic lesions, and it may be especially useful in NF2 patients to reduce cumulative morbidity.